New Improvement of Labor Accounting in the Sharing Economy. (13th January 2020) - Zhou, Yuanxiang; Yin, Weichuan
Abstract : The investigation of labor is a key aspect of population research, and labor accounting, as its foundation, is an important means to judge the degree of economic development and monitor the changes of the labor market, having always been a focus of scholarly research. At present, the sharing economy is on the rise worldwide and influences labor accounting. In this paper, starting from the context of the sharing economy and the current situation of labor accounting, several important aspects of labor accounting will be discussed. In the context of the sharing economy, household subsistence service production is to be included in the production accounting boundary, which is the root of the changes in labor accounting. On this basis, the following findings are drawn. (1) The scope of accounting for employment should be expanded, which puts higher demands on the labor accounting method. (2) Working time should be remeasured, especially indicators based on pay time. (3) Finally, the design of indicators in labor underutilization also requires the formation of new ideas, especially unemployment should be redefined. Finally, in view of the current status of labor accounting in China, policy suggestions for future improvement under the sharing economy are put forward.